2013
DOI: 10.3906/sag-1206-108
|View full text |Cite
|
Sign up to set email alerts
|

Does renal parenchymal thickness affect bleeding in percutaneous nephrolithotomy?

Abstract: Ion probe dating is used to determine the relative ages of amphibolite-facies meta-clastic sedimentary rocks and crosscutting granitoid rocks within an important 'basement' outcrop in northwestern Turkey. U-Pb ages of 89 detrital zircon grains separated from sillimanite-garnet micaschist from the Central Sakarya basement terrane range from 551 Ma (Ediacaran) to 2738 Ma (Neoarchean). Eighty fi ve percent of the ages are 90-110% concordant. Zircon populations cluster at ~550-750 Ma (28 grains), ~950-1050 Ma (27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 111 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Increased stone density was demonstrated to be associated with low stone-free rates, and fragmenting harder stones may also cause collecting system damage [11]. The results of previous studies on the effects of parenchymal thickness on PCNL outcomes revealed contradictory results [10,1214]. It is unclear whether parenchymal thickness, in combination with stone density measured by Hounsfield units, affects stone-free rates after PCNL.…”
Section: Introductionmentioning
confidence: 99%
“…Increased stone density was demonstrated to be associated with low stone-free rates, and fragmenting harder stones may also cause collecting system damage [11]. The results of previous studies on the effects of parenchymal thickness on PCNL outcomes revealed contradictory results [10,1214]. It is unclear whether parenchymal thickness, in combination with stone density measured by Hounsfield units, affects stone-free rates after PCNL.…”
Section: Introductionmentioning
confidence: 99%